Pengetahuan Ibu Tentang Makanan Pendamping ASI (MP-ASI) - Yuna Trisuci Aprillia; Endang Siti Mawarni; Santi Agustina (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Mothers have an important role in the growth and development of babies and toddlers, especially mother's knowledge has an influence on the mindset and level of care to provide proper food intake for their children. Infants and toddlers are included in the nutrition-prone group in the community where the highest prevalence of malnutrition is in infants and toddlers. The prevalence rate in the West Java region for malnutrition is still above 14% and the stunting rate is still above the national rate, namely 31%. This research is descriptive-analytic with a cross-sectional design. Data collection was carried out using a questionnaire. The number of population and sample is 35 respondents. The conclusion of this research is that the parity variable is the most dominant variable or has a big influence on the knowledge of mothers about complementary foods so that mothers have been given the right information since pregnancy-related to exclusive breastfeeding and provision of complementary foods and can seek information using technology or device to be able to access information on the right complementary foods.